The exhibition is just the beginning : Qualitative analysis of creative educational materials prepared by preservice teachers - Echegoyen Sanz, Yolanda; Martín Ezpeleta, Antonio (Journal of Education Culture and Society, 2020)
Aim. The aim of this work is to present a qualitative analysis of the creative educational materials prepared by preservice teachers in the context of an educational experience around a museum exhibition about Science and Literature, described in a previous work (Authors, 2020). The responses to a final questionnaire about interdisciplinarity, integration of Sciences and Arts or the use of museums for children’s education are also analysed.Methods. The participants were 121 alumni of two different subjects “Natural Sciences for teachers” and “Literary training for teachers” at a Spanish university. Preservice teachers had to select an item of the museum exhibition and, as a group, prepare a catalogue intended for children, where they had to write a short text related to the object and activities for children in an exercise of didactic transposition. The students generated teaching materials with a high component of creativity and a multimodal approach, with a mixture of linguistic and non-linguistic codes. The qualitative analysis of these creative teaching materials was carried out with Atlas.ti v8. To assess the experience a questionnaire about different aspects of the proposal was completed by the students at the end of the semester.Results and conclusion. The analysis of the teaching materials demonstrates differences between the alumni attending both subjects in the type of items selected, the literary genre of the short text and the prepared activities. The responses to the final questionnaire give us an insight on the reasons for the item selection and show how most of the students considered the experience as very interesting and formative. We can conclude that the educational experience here described served as an exercise to internalise the benefits of this method and, at the same time, adapt it for their future students in Primary Education.